STRATEGIC INFORMATION SYSTEMS PLANNING USING THE WARD AND PEPPARD METHOD (A CASE STUDY OF KOPERASI DAUH AYU) - Biantara, I Gede Dody Okta; Divayana, Dewa Gede Hendra; Dewi, Luh Joni Erawati (Information Technology and Science (ITScience), 2025)
Koperasi Dauh Ayu requires a formally articulated IS/IT strategy to overcome fragmented, manual operations and move toward an integrated, member-centric model. This case study applies the Ward and Peppard framework to diagnose business and IS/IT conditions, using PEST, Porter’s Five Forces, value chain, technology trend scanning, and SWOT with quantitative IFAS–EFAS scoring from six expert respondents. The cooperative is positioned in Quadrant I of the SWOT map with coordinates X = 0.309 and Y = 0.397, indicating an aggressive strategy space where internal strengths can be leveraged to seize external opportunities. The study produces a prioritized portfolio of fourteen applications mapped with the McFarlan Grid, alongside an IT strategy for network, hardware, and platform modernization, and an IS/IT management strategy that establishes a dedicated ICT unit and governance mechanisms. Recommended initiatives are expected to reduce cycle times and error incidence, consolidate a single source of truth for member and financial data, and elevate service quality. The contribution extends the application of Ward and Peppard to the cooperative sector in Indonesia, a context less examined than large enterprises, and shows how staged capability building can translate environmental enablers into realized digital benefits. Limitations include a single-case design without post-implementation measurement; future work should pilot priority systems and evaluate pre–post performance and cost–benefit outcomes.